Biodiesel production from castor oil using potassium hydroxide as a catalyst: Simulation and validation. Issue 19 (1st October 2016) - Thirugnanasambandham, K.; Shine, K.; Agatheeshwaren, A.; Sivakumar, V.
ABSTRACT: The key objective of the present research is to optimize and investigate the biodiesel production from ricinuscommunis (castor) oil using microwave-assisted hybrid transesterfication process under various conditions such as microwave power, treatment time, ethanol:oil ratio and catalyst concentration (KOH). Response surface methodology (RSM) coupled with four factors with a three-level Box–Behnken response surface design (BBD) was employed to model the transesterfication technique. The obtained results were analyzed by analysis of variance (ANOVA) and a second-order polynomial model was developed to study the interactive effect of process factors on biodiesel production. Derringer's desired function methodology was used for the optimization and optimum conditions for maximizing the biodiesel production. Under optimum conditions, the predicted biodiesel production was found to be 95% with a desirability value of 0.998. The fuel properties of the produced biodiesel were compared with the ASTM D6751 standards.